Judicialização da saúde: um olhar sobre a reabilitação no município de Betim/MG - Luciana Fernandes Freitas Januzzi (2022)
In Brazil, since the year 2000, there has been a clear influence of the Judiciary in decisions applicable to the other powers and the judicialization becomes a mean to guarantee individual rights, such as the right to healthcare. This phenomenon generates a commitment of the public budget that starts to be destined for the cost of individual benefits. In healthcare, the medium complexity, in which specialized outpatient rehabilitation care is inserted, suffers from little investment by governors. Difficulty in accessing secondary healthcare, such as rehabilitation services, increases the supressed demand and the long waiting time for assistance, causing an increase in the volume of lawsuits. The number of lawsuits related to rehabilitation may be directly related to users’ dissatisfaction with the physical therapy assistance offered by the SUS in Betim (MG). Therefore, the objective of this study was to analyze the profile of lawsuits filed against the Betim Municipal Health Department, associated with physiotherapeutic procedures, between 2015 and 2019. A descriptive cross-sectional observational study was carried out, parallel to documentary research. In the studied period, a total of 26 processes related to physical therapy rehabilitation were identified. We found that 17 beneficiaries had care records from the Rehabilitation Center and, among these, 9 responded to the satisfaction questionnaire regarding treatment at the CRR. The questionnaire - MedRisk - was applied on a 5-point Likert scale. A descriptive analysis of the data and calculation of the Sperman coefficient were carried out at a significance level of 5%, using the SPSS ® software, version 19. We observed that the representation of most cases in the Judiciary was by private lawyers (76 .9%), the prescription was signed by medical professionals from another location different from the defendant's residence (79.2%) and that the beneficiaries of the rehabilitation processes requested services and supplies not available in the SUS table (80.8%). Regarding the respondents of the satisfaction questionnaire with physiotherapeutic care, most were women (77.8%), that were responsible for minors treated at the CRR (66.7%), with a predominance of neurological disorders (88%). Most respondents reported satisfaction with the services offered by the CRR. Items related to patient’s convenience and education showed a lower value for satisfaction, while questions about interpersonal relationships between professionals and employees with users were well evaluated. There was no correlation between perceived functional status and MedRisk score (p=0.09). We concluded that people who resort to the Judiciary, claiming some service or product related to rehabilitation, are mostly women, responsible for minors who find in the judicial route hope to guarantee a better quality of life for their children with chronic neurological disorders. As technical products, two Technical Reports were developed, addressed to the Municipal Health Council and to the Public Prosecutor's Office of the Municipality of Betim.